Evaluation of the Effects of Multifocal Intraocular Lens Oculentis LENTIS Mplus LS-313 MF30 on Visual Performance in Patients Affected by Bilateral Cataract and Treated with Phacoemulsification - R. Nuzzi; F. Tripoli; A. Ghilardi (Journal of Ophthalmology)
Background. The purpose of this study was to evaluate the visual results and patients’ satisfaction with surgical treatment of phacoemulsification and implantation of the innovative intraocular multifocal lens (MFIOL) Oculentis LENTIS Mplus MF30 in patients with bilateral cataracts. Materials and Methods. A single-center prospective observational study was conducted on a total of 20 patients with bilateral cataracts. We evaluated the monocular UCVA and BCVA at 1 day, 7 days, 1 month, 3 months, and 6 months at different distances after phacoemulsification and MFIOL implantation and the binocular UCVA at the same distances. We also assessed the frequency of visual disturbances, overall visual satisfaction, spectacles dependence, and ease of performing different daily activities. Results. The MFIOL Mplus MF30 was able to significantly improve the monocular UCVA and BCVA at all working distances. Overall visual satisfaction was above 9/10 in all postoperative observation intervals. The degree of independence from spectacles at all distances was 100%. The frequency of adverse visual phenomena was minimal. Conclusions. In accordance with the literature, the Oculentis LENTIS Mplus MF30 has proved to be a valid therapeutic alternative for visual rehabilitation after phacoemulsification of the cataract in patients also wishing to treat presbyopia, at the cost of very few visual adverse effects. Trials Registration. This trial is registered with ISRCTN20862627.